О ПРОБЛЕМАХ И ПЕРСПЕКТИВАХ ДЕЯТЕЛЬНОСТИ КИТАЙСКИХ ПРЕДПРИНИМАТЕЛЕЙ В КАЗАХСТАНЕ - Бектурганова, П. Е.; Джадайбаева, З. (Journal of Oriental Studies, 2016)
Мақалада Қытай кәсіпкерлерінің Қазақстан Респуб-ликасында айналысып жүрген қызметіне сипаттама бе-рілген, олардың негізгі кәсіпкерлік бағыттары, іс жүр-гізудегі ұлттық ерекшеліктері сарапталған. Қазақстан-дағы Қытай кәсіпкерлерінің негізгі мәселелері қарасты-рылған.In article attempt to present an overall picture of presenceof Chinese businessmen in the Republic of Kazakhstanmarket becomes. Give the characteristic to specificity ofbusiness dealing of east partner. Fields of activity of Chinesebusinessmen in Kazakhstan are considered. Problems andprospects in development of Chinese business in RepublicKazakhstan are discussed.